Intracellular polyphosphate levels in gluconacetobacter diazotrophicus affect tolerance to abiotic stressors and biofilm formation - Grillo Puertas, Mariana (2018)
Gluconacetobacter diazotrophicus is a plant growth-promoting bacterium, used as a bioinoculant. Phosphate (Pi) modulates polyphosphate (polyP) levels in Escherichia coli, affecting cellular fitness and biofilm formation capacity. Can environmental Pi modulate polyP levels in G. diazotrophicus to enhance fitness in view of its technological applications? In high Pi media, cells were able to accumulate polyP and to degrade it, improving survival, tolerance to stressors, biofilm formation capacity on abiotic and biotic surfaces and competence as a growth promoter of strawberry plant. Findings contribute to the importance of Pi and intracellular polyP as signals involved in the survival of G. diazotrophicus.